Biological effects of naringenin and naringin: a review of bioassays (Research, Society and Development, 2023)
Currently, the search for natural antimicrobial compounds has increased and, taking into account the high rate of infection by antibiotic-resistant microorganisms, the search for new compounds that have an antimicrobial effect has been stimulated. Flavonoids fit into this group because of their strong biological and medicinal properties. Biological activity such as anti-inflammatory, antioxidant, antibacterial, anti-hepatotoxic, and anti-carcinogenic are reported to occur. The objective of the current study was to collect information on the in vitro antibacterial activity of the flavonoids naringenin and naringin and to demonstrate the biological effects of these substances against bacteria. This is a integrative review of the literature on scientific articles published between 2017 and 2022 that was done using the PUMED databases. Flavonoids may be able to inhibit bacterial growth through different mechanisms, such as changing membrane and wall permeability cell, inhibition of nucleic acid synthesis and also by synergistic activity with antibiotics. The development of new antimicrobial drugs is increasingly necessary, which makes flavonoids promising candidates. Therefore, it is believed in the potential of naringenin and naringin as candidate phytoconstituents for the development and innovation of new antibiotics.